Identification of Superior Plantation Commodities for Economic Growth in Musi Banyuasin (Muba) Regency, South Sumatra - Thomas Christofora Gunarto; Lady Christina (Law and Economics, 2024)
The research on the identification of superior plantation commodities for economic growth in Musi Banyuasin (Muba) Regency, South Sumatra, provides insights into the economic, social, and environmental dimensions of the plantation sector in the region. Through a mixed-methods approach, this research explores the current state of the plantation industry, emerging opportunities, challenges, and criteria for identifying superior commodities. The findings of the research highlight palm oil and rubber as dominant commodities in Muba Regency, with established supply chains, market demand, and government support. These commodities have high economic potential but face challenges related to land availability, environmental concerns, and labor issues. Coffee and spices are identified as emerging commodities with growing demand in domestic and international markets. These commodities offer opportunities for value addition and differentiation but require investments in processing and marketing infrastructure. The research underscores the importance of diversifying the plantation sector to promote sustainable and inclusive economic growth. Addressing challenges related to land availability, environmental concerns, labor issues, market access, access to finance and technology, competition, and policy and regulatory constraints is crucial for unlocking the full economic potential of the plantation sector.